Wisdom, not veritism - RYAN, Shane (Institutional Knowledge at Singapore Management University, 2021)
In this response to Pritchard's "In Defence of Veritism", I defend the view that it is wisdom rather than truth that is fundamental in epistemology. Given that recent philosophical discussions of the nature of wisdom may be unfamiliar to some epistemologists, a brief overview of these discussions is provided and that which is relevant for the subsequent discussion in this piece is highlighted. I explain that scholars working on the topic tend to accept that wisdom comprises at least one familiar epistemic standing and that, unlike other epistemic goods, wisdom is thought to be tied to a narrowly specified content. I clarify the philosophical ques-tion to which veritism is the proposed answer and clarify the different senses of fundamental in play in that question. As Pritchard points out, fundamentality in epistemology concern both concep-tual and axiological claims. Next, I explicate Pritchard's veritism, his defence of the claim that truth is fundamental in epistemol-ogy, explaining the case made for it's superiority over the consid-ered alternatives. One alternative I consider is that there is no fundamental good in epistemology, either conceptually or axio-logically. I examine whether Pritchard can reject truth equality successfully while maintaining his monism with regard to what he takes to be epistemically fundamental. Indeed, while Pritchard's appeal to the intellectually virtuous inquirer here seems appro-priate, his view that this ultimately provides support to his truth monism is less convincing for reasons that will be explored. I fol-low up this discussion by arguing that an appeal to the intellectu-ally virtuous agent better lends support to wisdom as episte-mically fundamental, rather than Pritchard's veritism. I make the point that Pritchard's claim that the intellectually virtuous agent loves the truth is plausible but I question whether it's also plausi-ble that the love of the intellectually virtuous agent stops at the truth. Rather, I claim that such an agent ultimately loves wisdom. In fact, wisdom seems likely to be the highest good prized by the intellectually virtuous agent - the good that they strive to attain or become better with regard to across a lifetime. In support of this claim, I point out that wisdom is the most prized of all epis-temic goods.